Camel milk and milk products - Andreja Brezovečki; Mateja Čagalj; Zrinka Filipović Dermit; Nataša Mikulec; Darija Bendelja Ljoljić; Neven Antunac (Mljekarstvo)
Camel milk and camel milk products have always been highly esteemed playing even today an important role in the diet of the population in the rural areas of Africa, Asia and the Middle East, with scarce agricultural areas, high temperatures and small amount of precipitation. In aggravated environmental circumstances, camels may produce more milk than any other species, while their demand for food is very modest. A camel produces between 1000 and 2000 L of milk during the lactation period of 8 to 18 months, while the daily production of milk is between 3 and 10 L. The goal of the overview is to present the chemical composition of camel milk, and products made from camel milk. On average camel milk contains 81.4-87 % water, 10.4 % dry matter, 1.2-6.4 % milk fat, 2.15-4.90 % protein, 1.63-2.76 % casein, 0.65-0.80 % whey protein, 2.90-5.80 % lactose and 0.60-0.90 % ash. Variations in the contents of camel milk may be attributed to several factors such as analytical methods, geographical area, nutrition conditions, breed, lactation stage, age and number of calvings. Camel milk is becoming an increasingly interesting product in the world, not only for its good nutritive properties, but also for its interesting and tasteful products.